KUALITAS PELAYANAN CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH DI BANK BRI UNIT MANDREHE - Melsy Nathania Daeli; Juan Exsaudia Sihombing; Elsa Elsita Khoerunisa; Rukiah Natasya Sihite; Zefanya Putri Sianipar; Hamonangan Siallagan; Christnova Hasugian (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
Service quality is a unique phenomenon, because the dimensions and indicators can vary in each community involved in the service. BRI Mandrehe unit prioritizes the quality of service provided in the form of speed and comfort provided to customers. One form of problem that is a phenomenon experienced by customers and needs to be a main concern For banks, what must always be improved and improved so that bank performance becomes more productive is the queue that occurs when waiting for banking services. This research aims to determine the quality of customer service on customer satisfaction at the Mandrehe unit of BRI Bank. In this research the data used is primary data. The type of data in this research is secondary data. The data collection methods in this research are field studies and literature studies. The method used is descriptive qualitative. The results of this research are, firstly, customer service plays an important role in providing the best service to customers. Therefore, Bank BRI Mandrehe unit prioritizes the appearance of its customer service standards, such as dressing politely, neatly and neatly. Second, customer service as a communicator is responsible for providing all information about bank products or services to customers, accommodating customer complaints and objections. BRI Mandrehe unit prioritizes customer service in carrying out tasks in accordance with standard operating procedures. For this reason, BRI Mandrehe unit customer service must be smiling, smooth, friendly, calm and patient in serving each customer.